If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x = 8x + -3 Reorder the terms: -4x = -3 + 8x Solving -4x = -3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4x + -8x = -3 + 8x + -8x Combine like terms: -4x + -8x = -12x -12x = -3 + 8x + -8x Combine like terms: 8x + -8x = 0 -12x = -3 + 0 -12x = -3 Divide each side by '-12'. x = 0.25 Simplifying x = 0.25
| 17+x-15=-9 | | 9x-15=5x-13 | | -6+3y=12 | | -13=2x-4x+3 | | 5(1-4)=3(1+2) | | 5x-80=2x-11 | | y=-12x+24 | | 50x+2y=50 | | 0.16b=-12 | | -16=3x-5x-2 | | 3(2m)=x | | 20x-18=54-16x | | 3x+8y+9x+y=90 | | 8=5g-2 | | 6-5x+7x=24 | | 13x-4=2x+16 | | -17=7d-8 | | 45=198-3x | | 2x+3=-x-3 | | 9x^2+68x+159=0 | | 9+4x=36 | | 4(5-2)=48 | | 5x-59=10x+71 | | 27+2.5x=4x | | -10-4x+7x=4 | | 7C+10=28 | | x=3.25 | | 0.05-0.01(x+1)=0.01(2-x) | | 4+12=-2*6-2*4a | | -2+5x=9+3x | | T=18-20 | | T=7-2 |